Association of Helicobacter pylori Infection with Glycemic Control in Patients with Diabetes: A Meta-Analysis - Chika Horikawa; Satoru Kodama; Kazuya Fujihara; Yoko Yachi; Shiro Tanaka; Akiko Suzuki; Osamu Hanyu; Hitoshi Shimano; Hirohito Sone (Journal of Diabetes Research)
Objective. To assess the association between Helicobacter pylori (HP) infection and glycemic control in patients with diabetes through a meta-analytic approach. Research Design and Methods. Electronic literature searches were conducted for cross-sectional studies that examined the hemoglobin A1c (A1C) level by whether patients with diabetes were or were not carriers of HP. Mean differences in A1C between groups with and without HP infection were pooled with a random-effects model. Results. Thirteen eligible studies were included in this meta-analysis. Overall, the HP carriers did not have significantly higher A1C levels compared with HP noncarriers (mean difference (95% CI), 0.19% (−0.18 to 0.46), P = 0.16). When the analysis was limited to studies targeting patients with type 1 diabetes, there was also no significant difference in A1C (0.69% (−0.31 to 1.68), P = 0.18). Conclusions. There was insufficient evidence that HP infection worsened glycemic control in patients with diabetes.